Thermodynamic calculations in alloys Ti-Al, Ti-Fe, Al-Fe and Ti-Al-Fe - Kostov Ana; Friedrich B.; Živković D. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Thermodynamic calculations of three binary Ti-based alloys: Ti-Al, Ti-Fe, and Al-Fe, as well as ternary alloy Ti-Al-Fe, is shown in this paper. Thermodynamic calculations involved thermodynamic determination of activities, coefficient of activities, partial and integral values for enthalpies and Gibbs energies of mixing and excess energies at different temperatures: 1873K, 2000K and 2073K, as well as calculated phase diagrams for the investigated binary and ternary systems. The FactSage is used for all thermodynamic calculations.